Arcuate Nucleus Orexin-A Signaling Alleviates Cisplatin-Induced Nausea and Vomiting Through the Paraventricular Nucleus of the Hypothalamus in Rats - Guo, Feifei; Gao, Shengli; Xu, Luo; Sun, Xiangrong; Zhang, Nana; Gong, Yanling; Luan, Xiao (Frontiers in Physiology, 2018)
The most common side effects of cisplatin chemotherapy are nausea and vomiting, and the overwhelming majority of research studies on the mechanism of cisplatin-induced nausea have been focused on the “vomiting center.” As a modulatory center of gastric motility, the roles of the hypothalamus in nausea and vomiting remain unclear. In the present study, we investigated the effects of exogenous orexin-A injected into the arcuate nucleus on cisplatin-induced nausea and vomiting, and the possible underlying mechanism. Kaolin intake was calculated daily in cisplatin-treated and saline-treated rats. Gastric motility recording, injections into the arcuate nucleus, and lesions of the paraventricular nucleus were used to study the effects of orexin-A and the hypothalamic nucleus on disorders of gastrointestinal function in cisplatin-treated rats. The pathway from the arcuate nucleus to the paraventricular nucleus was observed through Fluoro-Gold retrograde tracing. Furthermore, an NPY Y1 receptor antagonist was administered to explore the possible mechanisms involved in the effects of orexin-A in the arcuate nucleus. We illustrated that exogenous orexin-A injected into the arcuate nucleus reduced kaolin intake and promoted gastric motility in cisplatin-treated rats, and these effects could have been blocked by an ipsilateral paraventricular nucleus lesion or co-injected antagonist of orexin-A-SB334867. Additional results showed that orexin-A-activated neurons in the arcuate nucleus communicated directly with other neurons in the paraventricular nucleus that express neuropeptide Y. Furthermore, activation of the downstream neuropeptide Y pathway was required for the observed effects of orexin in the arcuate nucleus on cisplatin-induced nausea and vomiting. These findings reveal a novel neurobiological circuit from the arcuate nucleus to the paraventricular nucleus that might provide a potential target for the prevention and treatment of cisplatin-induced nausea and vomiting.